NAFLD and nutraceuticals: a review of completed phase III and IV clinical trials - Hegazi, Omar E.; Alalalmeh, Samer O.; Alnuaimi, Ghala Rashid Humaid; Shahwan, Moyad; Jairoun, Ammar Abdulrahman; Alorfi, Nasser M.; Majrashi, Shaker A.; Alkhanani, Mustfa Faisal; Alkhattabi, Abdullah; Alourfi, Mansour M.; Alsolami, Faris A.; Alsharif, Saeed; et al. (Frontiers in Medicine, 2023)
Background Nonalcoholic Fatty Liver Disease (NAFLD) has become a significant public health concern, affecting approximately one-fourth of the population. Despite its prevalence, no FDA-approved drug treatments specifically target NAFLD. Aim To provide a review of clinical trials investigating the use of herbal remedies and dietary supplements in NAFLD management, utilizing the ClinicalTrials.gov database. Methods This review evaluates the current evidence by examining completed phase III and IV clinical trials registered on ClinicalTrials.gov. An exhaustive search was performed on April 17, 2023, using the terms “Nonalcoholic Fatty Liver Disease” and “NAFLD.” Two independent reviewers appraised eligible trials based on pre-defined inclusion and exclusion criteria. Results An initial search yielded 1,226 clinical trials, with 12 meeting the inclusion criteria after filtration. The majority of trials focused on Omega-3 fatty acids (20.0%) and vitamin D (26.7%), followed by caffeine, chlorogenic acid, ginger, phosphatidylcholine, Trigonella Foenum-graecum seed extract, vitamin C, and vitamin E (each 6.7%). Most studies were Phase 3 (75.0%) and used a parallel assignment model (91.7%). Quadruple masking was the most prevalent technique (58.3%), and Iran was the leading country in terms of trial locations (25.0%). These interventions constitute two herbal interventions and nine supplement interventions. Conclusion This reveals a diverse range of nutraceuticals, with Omega-3 fatty acids and vitamin D being predominant in the management of NAFLD. The global distribution of trials highlights the widespread interest in these therapeutics. However, more rigorous, large-scale trials are needed to establish safety, efficacy, and optimal dosages.